2006
DOI: 10.1128/jvi.80.6.2913-2923.2006
|View full text |Cite
|
Sign up to set email alerts
|

West Nile Virus Evades Activation of Interferon Regulatory Factor 3 through RIG-I-Dependent and -Independent Pathways without Antagonizing Host Defense Signaling

Abstract: The ability of viruses to control and/or evade the host antiviral response is critical to the establishment of a productive infection. We have previously shown that West Nile virus NY (WNV-NY) delays activation of interferon regulatory factor 3 (IRF-3), a transcription factor critical to the initiation of the antiviral response. Here we demonstrate that the delayed activation of IRF-3 is essential for WNV-NY to achieve maximum virus production. Furthermore, WNV-NY utilizes a unique mechanism to control activat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
163
2
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 166 publications
(183 citation statements)
references
References 57 publications
(61 reference statements)
11
163
2
1
Order By: Relevance
“…irf7 is a member of the irf family, and irf members often function in host defense and inflammation [27][28][29][30]. An inflammation pathway might be involved in HSC and myeloid lineage differentiation in zebrafish [31,32].…”
Section: Decreased Gcsfr-nitric Oxide (No) Inflammation Signaling Migmentioning
confidence: 99%
“…irf7 is a member of the irf family, and irf members often function in host defense and inflammation [27][28][29][30]. An inflammation pathway might be involved in HSC and myeloid lineage differentiation in zebrafish [31,32].…”
Section: Decreased Gcsfr-nitric Oxide (No) Inflammation Signaling Migmentioning
confidence: 99%
“…The C-terminal regulatory domain binds with dsRNA resulting in conformational changes that lead to its oligomerisation and the subsequent interaction of RIG-1 with MAVS through a CARD-CARD interaction [80,83]. The role of RIG-1 in the production of type 1 IFNs has been demonstrated in numerous viruses including Newcastle disease virus, VSV, Sendai virus, HCV, Japanese encephalitis virus, influenza A virus, rabies virus, measles virus, and RSV [84][85][86][87][88][89][90][91]. Further, a role of RIG-1 in triggering the immune response has been demonstrated for numerous viruses including DENV serotype 2, WNV, RSV, and HCV [86,87,[92][93][94].…”
Section: Rig-1mentioning
confidence: 99%
“…The role of RIG-1 in the production of type 1 IFNs has been demonstrated in numerous viruses including Newcastle disease virus, VSV, Sendai virus, HCV, Japanese encephalitis virus, influenza A virus, rabies virus, measles virus, and RSV [84][85][86][87][88][89][90][91]. Further, a role of RIG-1 in triggering the immune response has been demonstrated for numerous viruses including DENV serotype 2, WNV, RSV, and HCV [86,87,[92][93][94]. It has been demonstrated that rhabdovirus VSV infection in murine DCs induces RIG-1-dependent production of IL-1b and IL-18 via NF-jB, caspase-1, and caspase-3 activation; thus, RIG-1 is an inflammasome activator.…”
Section: Rig-1mentioning
confidence: 99%
“…Rather, WNV delays activation of PRR signaling long enough to give the virus a replicative advantage within the infected cell [44]. The delayed activation of IRF-3 during WNV infection results in a robust α/β IFN response that slows cell to cell virus spread but this response is largely ineffective at limiting infection by the emergent strain [45].…”
Section: Wnv Regulation Of Ifn Signalingmentioning
confidence: 99%
“…Studies using cells from gene knockout mice revealed that WNV signals innate defenses through RIG-I-dependent mechanisms as well as through processes independent of RIG-I likely involving MDA5 [44]. These studies revealed that efficient viral replication is dependent upon the virus delaying the activation of innate defenses inasmuch as ectopic activation of the RIG-I pathway results in a severe limitation of virus replication [44]. The delay in PRR detection of WNV provides the virus with a window of opportunity to essentially replicate unimpeded during the early stages of infection.…”
Section: Wnv Regulation Of Ifn Signalingmentioning
confidence: 99%